Proceedings of the 12th International Symposium Continuous Surface Mining Aachen 2014 - Niemann-Delius, Christian (Springer International Publishing, 2015)
This edited volume contains research results presented at the 12th International Symposium Continuous Surface Mining, ISCSM Aachen 2014. The target audience primarily comprises researchers in the lignite mining industry and practitioners in this field but the book may also be beneficial for graduate students.